Comparison of Workflow, Maintenance, and Consumables in the GeneXpert Infinity 80 and Panther Instruments While Testing for Chlamydia trachomatis and Neisseria gonorrhoeae. Issue 6 (June 2016) - Jang, Dan; Ratnam, Sam; Gilchrist, Jodi; Arias, Manuel; Smieja, Marek; Mayne, Donna; Chernesky, Max A.
Abstract : Background: The 2015 Sexually Transmitted Diseases Treatment Guidelines from the Centers for Disease Control and Prevention recommend testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) using nucleic acid amplification tests, and prompt treatment of infected persons on site under direct observation. Faster time to results may enable treatment and management outcomes. Methods: Workflow parameters for processing 1, 10, 48, 96, and 192 tests were determined in the GeneXpert Infinity 80 (Cepheid) and Panther (Hologic) instruments. Results: In an Xpert CT/NG cartridge, the time to first results on the Infinity 80 was 1 hour 30 minutes for single or multiple tests and final results for 10, 48, 96, and 192 tests were available at 1 hour 37 minutes, 1 hour 54 minutes, 3 hour 17 minutes, and 5 hour 7 minutes, respectively. With the Aptima CT/GC assay on the Panther, the respective times were 3 hr 45 min for the first test result, and 3 hour 51 minutes, 4 hour 38 minutes, 5 hour 26 minutes, and 7 hour 4 minutes to final results. The Panther required more time for maintenance and consumed a greater variety of plastics and reagents but required less hands-on time when testing larger numbers of specimens. Conclusions: The Infinity 80 is a versatile instrument for continuous random access testing of small or large numbers of clinical specimens and may provide diagnostic results, in some settings, in time for treatment of CT and NG infections. Abstract : The GeneXpert Infinity 80 had less hands-on time and reported results earlier than the Panther, which required more maintenance, consumed more plastics and reagents but showed a lesser increment of total hands-on time as the number of specimens increased.